2013
DOI: 10.1002/grl.50601
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic offsets due to the 11 April 2012 Indian Ocean earthquakes (Mw 8.6 and 8.2) derived from GPS measurements

Abstract: The 11 April 2012 earthquake (Mw 8.6) in the Indian Ocean, about 100 km west off the Sumatra subduction zone, is the largest intraplate strike‐slip earthquake in the known history. Two hours later, it triggered another great earthquake of Mw 8.2 in its vicinity. The earthquakes reflect the internal deformation of the diffused plate boundary between India and Australia caused by the differential plate motion between them. The slip occurred on conjugate planes, and the presence of some of them has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…In 2001, the Indian region of Gujarat was affected by a strong Mw 7.7 intraplate earthquake, causing more than 20,000 casualties [9]. Finally, in 2012, the largest known strike-slip intraplate earthquake (Mw 8.6) occurred in the Indian Ocean, about 100 km SW of the Sumatra subduction zone [10]. With respect to the more common earthquakes occurring at plate boundaries, intraplate earthquakes are poorly understood as most of them are not easily ascribable to any identifiable or prominent fault zone.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, the Indian region of Gujarat was affected by a strong Mw 7.7 intraplate earthquake, causing more than 20,000 casualties [9]. Finally, in 2012, the largest known strike-slip intraplate earthquake (Mw 8.6) occurred in the Indian Ocean, about 100 km SW of the Sumatra subduction zone [10]. With respect to the more common earthquakes occurring at plate boundaries, intraplate earthquakes are poorly understood as most of them are not easily ascribable to any identifiable or prominent fault zone.…”
Section: Introductionmentioning
confidence: 99%
“…Seismicity map is based on BMKG (Agency for Meteorology, Climatology and Geophysics) database (lower detection limit is approximately M w 4.5). b Coseismic offsets resulting from the April 11, 2012 earthquake derived from AGNeSS (blue arrows) and two previous studies (gray arrows) (Yadav et al 2013;Hill et al 2015). Ishii et al 2013).…”
Section: Resultsmentioning
confidence: 95%
“…Ishii et al 2013). Previous studies (Yadav et al 2013;Hill et al 2015) reported co-seismic offsets around the Andaman-Nicobar GNSS network, which includes the Sumatran GNSS Array (SuGAr) and IGS sites. The AGNeSS also observed horizontal co-seismic offsets ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to identify the presence, size and activity extent of seismic faults for prevention and mitigation of earthquake-related disasters. Investigation of intracrustal faults is important not only to understand their relationships with intracrustal earthquakes (e.g., Yadav et al 2013) but also the contribution of fluid interactions between the mantle and crust in generating earthquakes (e.g., Sano et al 2014).…”
Section: Introductionmentioning
confidence: 99%